2006
DOI: 10.1007/s00226-006-0087-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of a two-stage heat treatment process: durability aspects

Abstract: Heat treatment of wood at relatively high temperatures (in the range of 150-280 degrees C) is an effective method to improve biological durability of wood. This study was performed to investigate the effect of heat treatment process optimisation on the resistance against fungal attack, including basidiomycetes, molds and blue stain fungi. An industrially used two-stage heat treatment method under relatively mild conditions (< 200 degrees C) was used to treat the boards. Heat treatment of radiata pine sapwood r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
1
19

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(126 citation statements)
references
References 36 publications
4
102
1
19
Order By: Relevance
“…Figure 4 shows the comparison between the different treatments and highlighted the significant differences. The TM wood studied here indicated that heat treatment did not obviously reduce, but rather accelerated the mold growth on the outer surface of the boards and the result is in agreement with other findings [1]. This effect might be due to the hemicellulose that hydrolyzed into oligomeric and monomeric structures even though it changes the cellulose, hemicelluloses and lignin content [1,31].…”
Section: Accelerated Mold Testsupporting
confidence: 90%
See 2 more Smart Citations
“…Figure 4 shows the comparison between the different treatments and highlighted the significant differences. The TM wood studied here indicated that heat treatment did not obviously reduce, but rather accelerated the mold growth on the outer surface of the boards and the result is in agreement with other findings [1]. This effect might be due to the hemicellulose that hydrolyzed into oligomeric and monomeric structures even though it changes the cellulose, hemicelluloses and lignin content [1,31].…”
Section: Accelerated Mold Testsupporting
confidence: 90%
“…To determine the water uptake capacity and swelling properties, the samples were oven-dried at 50°C for 72 h and submerged in distilled water at 21°C for periods of 1,3,6,12,24,48,96,192, 384 and 768 h. The distilled water was replaced after every soaking interval. After each saturation period, the masses and volumes were recorded to measure water absorption (WA; defined as the absorbed water divided by the dried mass) and volumetric swelling coefficient (S).…”
Section: Water Repellency and Dimensional Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…As pointed out above, brown rot fungi degrade hemicelluloses before cellulose (Militz 2002;Weiland and Guyonnet 2003;Rowell et al 2009) and this order of degradation is considered by many investigators to be a key step (Boonstra et al 2007;Rowell et al 2009). Rowell et al (2009) proposed that arabinose, which is the only L-pentose sugar found in wood, is a key compound that triggers the chain reactions of degradation and that its absence would prevent the initiation of degradation.…”
Section: Role Of Accessible Nutrientsmentioning
confidence: 99%
“…Rowell et al (2009) proposed that arabinose, which is the only L-pentose sugar found in wood, is a key compound that triggers the chain reactions of degradation and that its absence would prevent the initiation of degradation. Indeed, most hemicelluloses are degraded in thermally modified wood (Boonstra et al 2007) and hemicelluloses are considerably modified by acetyl groups in acetylated wood (Rowell et al 2009). …”
Section: Role Of Accessible Nutrientsmentioning
confidence: 99%